Bantuan PSU Perumahan bagi MBR pada Pelaksanaan Pekerjaan Jalan Lingkungan dengan Jenis Perkerasan Paving Block FC 20 M’pa - Taufik Halik, La Ode Muhammad; Hartani Minsi, Salfin; Umar, Sustriyani; Soeparyanto, Try Sugiyarto; Kadir, Ishak (Journal of Comprehensive Science, 2024)
the provision of PSU components for housing build public houses in the form of single houses or row houses, which stimulant in the housing location built by the perpetrator Development. For 2021, PSU assistance will be in the form of roads the environment in the housing built by the developer. Article 54 paragraph (3) letter (h) Law Number 1 of 2011 concerning Housing and Settlement Areas states that The government provides facilities and/or development assistance and acquisition of housing for MBR in the form of providing infrastructure, facilities and public utility (PSU). In order to follow up on the mandate of the provisions of Article 54 paragraph (3) of Law No.1 of 2011 referred to, Ministry Public Works and Public Housing through the Directorate General Housing carries out activities to provide PSU Housing assistance to MBR.